PROMOSI DAN HARGA PEMASARAN SEBAGAI FAKTOR DASAR UNTUK MEMPERTAHANKAN KEUNGGULAN KOMPETITIF PRODUK PERUSAHAAN PROPERTI. STUDI KASUS: PROPERTINDO WIJAYA PERKASA - Hasan, Samsurijal (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
The world and human being were changes rapidly against the development of society. Currently, the house is not only interpreted as a place to live individually, but the ownership of the house or land is considered as an investment item in the long run, especially for a middle and upper society which is often used as a benchmark of human welfare. This study was focusing to determine and analyze the marketing promotion and price as a fundamental factor in maintaining a competitive advantage of property company product. Propertindo Wijaya Perkasa was chosen as a case study. This analysis was used two main data which are Questioner as primary data along with company report as secondary data. Based on this study, the Marketing Promotion and Price is the Fundamental Factor to Maintaining A Competitive Advantage of Property Company Product, According to F test obtained that the independent variables (Product Quality, Price, Promotion and Service Quality) significantly influence competitive advantage at PT. Propertindo Wijaya Perkasa. While, based on the partial t-test, it is obtained that the value of t count is greater than t table with df = n-2 obtained by the value of t table = 2.034 (Î± = 0.05) meaning that the independent variables (product quality, price, promotion and service quality) have a significant effect on competitive advantage for the company. Also, the relationship between the independent variable and the dependent variable, namely there is a strong relationship, with the contribution of the independent variable to the dependent variable of 0.782. The coefficient of determination is 56.00% while 44.00% is influenced by other variables not included in this study.